2018
DOI: 10.9788/tp2018.1-10en
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducation for Attention Defi cit/Hyperactivity Disorder: What, How and Who Shall We Inform?

Abstract: The aim of this study was to review scientifi c publications about Attention Defi cit/Hyperactivity Disorder (ADHD) psychoeducation. A systematic review of literature was performed in eight national and international databases (Scielo Brazil, Index Psi, Pepsic, Lilacs, ScienceDirect, PsycINFO, Medline, and Scopus) using the combination of ADHD and psychoeducation as keywords. In total, 504 studies were found, although only 29 met the inclusion criteria. Afterwards, the information was organized into categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The findings of this scoping review underscore the positive influence of psychoeducational group interventions on adults with ADHD, particularly in improving ADHD symptoms. These results align with those of Nimmo-Smith et al (2020) [ 20 ], Oliveira et al (2018) [ 74 ], and Montoya et al (2011) [ 30 ], who found that non-pharmacological interventions improve ADHD symptoms among children [ 30 ] and adults with ADHD [ 20 , 74 ]. Moreover, the positive outcomes reported in this scoping review align with previous research highlighting the effectiveness of psychoeducational interventions in other psychiatric conditions.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this scoping review underscore the positive influence of psychoeducational group interventions on adults with ADHD, particularly in improving ADHD symptoms. These results align with those of Nimmo-Smith et al (2020) [ 20 ], Oliveira et al (2018) [ 74 ], and Montoya et al (2011) [ 30 ], who found that non-pharmacological interventions improve ADHD symptoms among children [ 30 ] and adults with ADHD [ 20 , 74 ]. Moreover, the positive outcomes reported in this scoping review align with previous research highlighting the effectiveness of psychoeducational interventions in other psychiatric conditions.…”
Section: Discussionsupporting
confidence: 89%
“…One possible consequence is that children diagnosed with ADHD and their parents might be confused. One of the main aims of psychoeducation is to help children and parents better understand their problems and subsequently promote better coping [37][38][39]. Yet, if the information provided is conflicting, children and parents may well be left with incoherent integration of the information provided and feel confused as to how to understand themselves or their children.…”
Section: Discussionmentioning
confidence: 99%
“…Psychoeducational interventions aim to increase patients’ knowledge and acceptance of their health condition [23]. Providing information about ADHD, its treatment, and symptom management strategies improves treatment satisfaction and treatment adherence, and enhances self-esteem and quality of life [19, 24]. Among the studies conducted with adults, positive results were obtained regarding inattention symptoms [25, 26], self-esteem [27, 28], anxiety and depressive symptoms [27, 29], and relationships with others [28, 29].…”
Section: Introductionmentioning
confidence: 99%